Interface design principles, elements and characteristics in multimedia teaching aid for non-creative design field in Malaysian tertiary education / Shahrunizam Sulaiman - Sulaiman, Shahrunizam (2019)
Process of teaching and learning involves the delivery of teaching and learning content which requires both a Lecturer and students. The development of media rich IT environment has developed sets of aptitude and attitude for students of Generation Y and beyond. As learning content become more complex, with demanding challenges and multidisciplinary curriculum, it is essential that the multimedia teaching aid is well developed to ensure the learning engagement is enhanced. In significance to this development, lecturers as the interface designer are facing new challenges, due to the importance of having a better understanding towards interactive multimedia teaching aid design which impacts a learning engagement. This research project is intended to explore and ascertain perceptions and experiences of lecturers understanding in designing the interface of a multimedia teaching aid. Data were collected from various sources, primary, and secondary through several complementing methods. This includes, contextual document analysis, content analysis of the multimedia teaching aid, and in-depth interview among lecturers from non-creative design field of studies in Malaysian public and private tertiary institutions. The data produced is being inductively analysed through interpretation of the meaning from the arising perceptions.